Use Of The Analytic Hierarchy Process Method To Determine Housing Locations - Ruth Amberly (International Journal of Industrial Innovation and Mechanical Engineering, 2024)
Decision Support Systems (DSS) are systems that assist individuals in making decisions and are an approach to supporting decision making on a particular problem. One of the methods used in SPK is the Analytical Hierarchy Process (AHP), which is used to make scientific and rational decisions in solving complex problems and has various criteria. In this research, the author applies the AHP method to determine the location of new housing development in Central Lombok Regency. The criteria considered include land conditions, facilities, social and economic aspects, and land availability. The research results show that SPK using the AHP method can help developers choose the right location for housing development in Central Lombok Regency.